Agrobacteria deploy two classes of His-Me finger superfamily nuclease effectors exerting different antibacterial capacities against specific bacterial competitors - Santos, Mary Nia M.; Pintor, Katherine L.; Hsieh, Pei-Yu; Cheung, Yee-Wai; Sung, Li-Kang; Shih, Yu-Ling; Lai, Erh-Min (Frontiers in Microbiology, 2024)
Type VI secretion system (T6SS) assembles into a contractile nanomachine to inject effectors across bacterial membranes for secretion. Agrobacterium tumefaciens species complex is a group of soil inhabitants and phytopathogens that deploys T6SS as an antibacterial weapon against bacterial competitors at both inter-species and intra-species levels. A. tumefaciens strain 1D1609 genome encodes one main T6SS gene cluster and four vrgG genes (i.e. vgrGa-d), each encoding a spike protein as an effector carrier. Previous study reported that vgrGa-associated gene 2, named as v2a, encodes a His-Me finger nuclease toxin (also named as HNH/ ENDO VII nuclease) contributing to DNase-mediated antibacterial activity. However, the functions and roles of other putative effectors remain unknown. In this study, we identified vgrGcassociated gene 2 (v2c) that encodes another His-Me finger nuclease but with distinct SHH motif differed from AHH motif of V2a. We demonstrated that the ectopic expression of V2c caused growth inhibition, plasmid DNA degradation, and cell elongation in Escherichia coli. The cognate immunity protein, V3c, neutralizes the DNase activity and rescues phenotypes of the growth inhibition and cell elongation.Ectopic expression of V2c DNase-inactive variants retains the cell elongation phenotype while V2a induced cell elongation in a DNase-mediated manner. We also showed that the amino acids of conserved SHH and HNH motifs are responsible for the V2c DNase activity in vivo and in vitro. Notably, V2c also mediated the DNA degradation and cell elongation of target cell in the context of interbacterial competition.Importantly, V2a and V2c exhibit different capacities against different bacterial species and function synergistically to exert stronger antibacterial activity against the soft rot phytopathogen, Dickeya dadantii.